Ensuring fire safety: compliance tests for the use of polystyrene foam in facades systems - Šukys, Ritoldas; Stankiuvienė, Aušra; Stas, Serhiy; Skrodenis, Saulius Vytautas; Tyshchenko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2024)
Ensuring fire safety is the most important thing in the construction industry, especially when it comes to facade materials. The inherent flammability of polystyrene foam poses significant safety concerns, especially when integrated into facade systems. Therefore, the main focus is on meeting the strict flammability requirements set for construction products, which are assessed by applying rigorous test procedures. This study focuses on the fire resistance testing of a facade system using EPS 70 with graphite additives. The system has been evaluated according to the strict DIN 4102-20 standards. Tests were conducted under real-world conditions to gain insight into the performance of the EPS 70 in real-world fire scenarios. Temperature measurements were taken at various points in the facade system, including at least 3.5 meters above the combustion chamber. The results showed that the temperature does not exceed 500 °C, so it is possible to quantify the thermal properties of the material and the ability to prevent the vertical spread of fire. After the tests, detailed post-test inspections were carried out to evaluate the internal flame propagation after removing the top layer of plaster. The study confirms that polystyrene foam EPS 70 with graphite additives meets the fire safety requirements of DIN 4102-20, which suggests that it can be used more widely in building facades to improve fire safety in residential and commercial buildings. The study highlights the importance of adhering to installation standards, emphasizing the need for accurate installation practices. It also encourages the development of new composite materials with similar or improved fire safety properties, laying the foundation for further innovations in fire-resistant materials